2004
DOI: 10.1021/ic035173e
|View full text |Cite
|
Sign up to set email alerts
|

Myoglobin as an Efficient Electrocatalyst for Nitromethane Reduction

Abstract: Xenobiotic metabolizing heme enzymes are thought to take a crucial part in the activation of a variety of carcinogens, including nitro compounds, through catalytic electron-transfer reactions, especially under anaerobic conditions. Myoglobin (Mb), as a model heme enzyme, is found to act as an efficient electrocatalyst for the reduction of nitromethane in thin surfactant films on pyrolytic graphite electrodes. The electrocatalytic process is characterized by cyclic voltammetry. The Mb-Fe(II)-nitrosomethane comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The voltammogram shows two heme-based redox couples of iNOSoxy: the first corresponds to redox couple Fe 3+ /Fe 2+ and the second corresponds to the further reduction of Fe 2+ . Although this second reduction is not of importance in the electrochemical characterization of PEI/iNOSoxy in this work, we note that this behavior is typical of NOS oxygenases as well as other heme proteins that we investigated in the past. , …”
Section: Results and Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The voltammogram shows two heme-based redox couples of iNOSoxy: the first corresponds to redox couple Fe 3+ /Fe 2+ and the second corresponds to the further reduction of Fe 2+ . Although this second reduction is not of importance in the electrochemical characterization of PEI/iNOSoxy in this work, we note that this behavior is typical of NOS oxygenases as well as other heme proteins that we investigated in the past. , …”
Section: Results and Discussionmentioning
confidence: 75%
“…NOS oxygenases are redox active. Prior work in our lab has shown that films of iNOSoxy and nNOSoxy can exchange electrons with an underlying electrode. , Therefore, electrochemical analysis of PEI/iNOSoxy films on PG electrodes can be used to provide an estimate of overall amount of iNOSoxy adsorbed on PEI. This method offers us with an independent way to compare and contrast enzyme loadings for immobilizations conducted at pH 8.6 and 7.0.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitroso compounds are of relevant importance as a result of their broad range of applications, such as synthetic reagents, spin trapping compounds, or high-energy materials . Nitrosoalkanes are biochemically important as well, for example, they form stable complexes with Fe III heme enzymes after the biodegradation of aliphatic nitroalkanes, a process which seems to be involved in the carcinogenic activity of the nitro compounds …”
Section: Introductionmentioning
confidence: 99%